FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PROFITABILITAS BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2015-2017 - Furi Mutiara Nugraheni, 15.05.62.0016; Maryono, Maryono (Students' Journal of Accounting and Banking, 2018)
The purpose of this study is to analyze the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Net Interest Margin (NIM) on Profitability of Commercial Bank listed on the Indonesia Stock Exchange which measured by Return On Equity(ROE). The period used in this study is three years, from 2015 to 2017. The population used in this study are all commercial banks listed on the Indonesia Stock Exchange. Based on the purposive sampling technique this study obtained a sample of 25 companies. This study uses documentation method that obtained from the financial statements, published on the official website of Indonesia Stock Exchange, www.idx.co.id. The analysis technique used in this study is multiple linear regression. The results show that the variables of Capital Adequacy Ratio(CAR), Good Corporate Governance (GCG) , Non performing Loan (NPL), and Net Interest Margin (NIM) has simultaneously and partially effect on the Profitability. Keywords: Profitability,ROE, CAR,GCG, NPL,NIM